The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/2015ja021134
|View full text |Cite
|
Sign up to set email alerts
|

Storm time occurrence and spatial distribution of Pc4 poloidal ULF waves in the inner magnetosphere: A Van Allen Probes statistical study

Abstract: Poloidal ULF waves are capable of efficiently interacting with energetic particles in the ring current and the radiation belt. Using Van Allen Probes (Radiation Belt Storm Probes (RBSP)) data from October 2012 to July 2014, we investigate the spatial distribution and storm time occurrence of Pc4 (7–25 mHz) poloidal waves in the inner magnetosphere. Pc4 poloidal waves are sorted into two categories: waves with and without significant magnetic compressional components. Two types of poloidal waves have comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
84
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 72 publications
11
84
1
Order By: Relevance
“…Only weak spectral features are seen in the compressional B z component. Some pulsations observed during the three orbits might be categorized as compressional ones based on the classification of Dai et al (2015). They consider pulsations to be compressional for even very weak B p , i.e., for abs (B p /B r ) > 0.2.…”
Section: Spectral Characteristic Of the Pc4 Pulsationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only weak spectral features are seen in the compressional B z component. Some pulsations observed during the three orbits might be categorized as compressional ones based on the classification of Dai et al (2015). They consider pulsations to be compressional for even very weak B p , i.e., for abs (B p /B r ) > 0.2.…”
Section: Spectral Characteristic Of the Pc4 Pulsationsmentioning
confidence: 99%
“…Schäfer et al (2007Schäfer et al ( , 2008 reported that sometimes high-m Pc4 waves were actually seen near the plasmapause and suggested that they may be due to harmonics of poloidal mode eigen oscillations in a radially confined Alfvén resonance region at the inner or outer edges of the plasmapause. Dai et al (2015) noted that the effect of the plasmapause on the radial transmission of the poloidal waves is caused by the fact that the Alfvén speed changes rapidly across the radial direction. Eriksson et al (2005) reported three cases of poloidal Pc5 pulsations with large azimuthal number (m = 100) waves observed by Cluster that occurred in the dayside magnetosphere during magnetically quiet times from L = 4 to L = 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar wind dynamic pressure fluctuations can be a substantial source for magnetosphere ULF wave power [Kessel, 2008;Takahashi and Ukhorskiy, 2007;Dai et al, 2015]. Solar wind dynamic pressure fluctuations can be a substantial source for magnetosphere ULF wave power [Kessel, 2008;Takahashi and Ukhorskiy, 2007;Dai et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, motivated by a recent direct observation of poloidal standing Alfvén waves in Earth's magnetosphere by Dai et al (2013) (see also Dai et al, 2015;Takahashi et al, 2013;Liu et al, 2013Liu et al, , 2011, we extend our investigation to examine the poloidal-mode waves as well. In the case of a transverse poloidal mode, we show that the wave equation can also be cast as a KG form along a field line.…”
Section: Introductionmentioning
confidence: 99%